Teatralizacja: pogranicze życia i teatru - Braun, Kazimierz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
“Theatricality” is a term describing the use of theatrical means of expression in various domains of life. It is an added, spectacular, visual, performative, and dramatic element of different social events and activities. Theatricality it is an area where two entities—life and art—meet, which results either in conflict or in unification. Life transforms into theatre and theatre transforms into life. Theatricality is, thus, a transient region between life and art. Consequently, it is a model example of a border zone. From centuries theatricality was used as a means in the process of interhuman communication. It served to amplify and facilitate interhuman communication and gave it a specific meaning. Theatricality was also employed as a powerful instrument of manipulating and falsifying messages. In contemporary theatre artistic creation is the primary goal and aesthetics takes primacy over all other objectives and values motivating and permeating theatre work. In theatricality the reasons and goals of using theatrical and theatre-like means of expression are practical—such as, for example, religious, social, political, or commercial. Theatre aspires (not always successfully) to situating its works in the realm of art, on the universal and transhistorical level, while theatricality is practically oriented.
Theatricality: A border zone between life and theatre
Keywords: Theatricality; theatre; character; space (in theatre and in theatricality); time (in theatre and in theatricality); teatralizacja; teatr; postać; przestrzeń (w teatrze i w teatralizacji); czas (w teatrze i w teatralizacji)